A validated, sensitive electrophoretic method for the detection of activin receptor type II‐Fc fusion proteins in human blood. Issue 8 (6th April 2018) - Martin, L.; Zouhiri, N.; Audran, M.; Marchand, A.
Abstract: New therapeutic proteins that trap circulating members of the transforming growth factor (TGF) beta superfamily (activins and growth differentiation factors) show promising effects on erythropoiesis and muscular growth. They are dimeric recombinant fusion proteins composed of the extracellular domain of a human activin receptor (ActRIIA or IIB) linked to the Fc part of human IgG1. Sotatercept (ActRIIA‐Fc) and Luspatercept (a modified ActRIIB‐Fc) in particular are now in phase 2/3 of clinical trials against anemia and included in the prohibited list established by the World Anti‐Doping Agency. To prevent a potential misuse by athletes in the near future, a robust and sensitive method of detection is needed. We validated an approach adapted from an electrophoretic method used for the detection of recombinant erythropoietins that allowed detection of various ActRIIA‐Fc and ActRIIB‐Fc proteins, including variants produced in different cell types, after a single immuno‐extraction step. After separation by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS‐PAGE), an initial testing procedure performed by single‐blotting can indicate the presence of an ActRII‐Fc (indifferently type IIA or IIB). A confirmation performed by double‐blotting using different antibodies for detection allows a more precise identification of the type of ActRII‐Fc (IIA, IIB). Starting from a few hundred microliters of serum or plasma, this method is specific, sensitive, and easy to perform. It could easily be adopted by anti‐doping laboratories. Abstract : Both ActRIIA‐Fc and ActRIIB‐Fc proteins can be immuno‐extracted from serum or plasma in a single step. After separation by SDS‐PAGE and blotting, 2 pairs of antibodies were validated for the revelation of ActRII‐Fc proteins allowing an initial testing procedure (after a single‐blot: Identification of an ActRII‐Fc protein in the sample) and a confirmation procedure (after a double‐blot: Identification of ActRIIA‐Fc or ActRIIB‐Fc in the sample). The method is sensitive (ng/mL), robust, and applicable to doping control samples